FORENSIC MEDICAL ASPECTS OF COMPLICATIONS ARISING IN AESTHETIC AND RECONSTRUCTIVE PLASTIC SURGERY PROCEDURES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This article scientifically analyzes the forensic significance of complications arising from plastic surgery, their pathogenetic mechanisms, and issues related to improving forensic assessment criteria. With the widespread application of modern aesthetic and reconstructive plastic surgery, there has been a rise in medico-legal disputes concerning postoperative infectious processes, necrotic changes, thromboembolic events, neurotrophic disorders, aesthetic deformities, and functional deficiencies. The study provides a comprehensive examination of the clinical and morphological characteristics of post-plastic surgery complications, the harm they cause to the body, and their impact on the degree of bodily injury. Furthermore, objective and standardized evaluation criteria are proposed for application in forensic medical practice